Unani methods of cure in the Indian subcontinent: an analytical study - Arshad Islam, Islam (2018)
The history of medicine is bound with the history of civilization, representing the complex interactions of human communities, geography and the environment over time. South Asia has always been a vibrant melting pot of interactions between different peoples. Unani (‘Greek’) medicine is based on ancient Hellenic thought (via its interactions with Babylonian, Egyptian, Indian and Persian knowledge).Tibb-i-Unani is Arabic for ‘Greek medicine’, which became Unani as practised in the Indian Subcontinent, where it was developed and refined through systematic experimentation by renowned scholars. Islamic physicians tested Indian traditional medicines using clinical trials, as a result of which they incorporated a number of indigenous medicines in their own system, advancing and enriching its treasures. The basic Unani framework is timeless, based on human action and intrinsic causes. This paper highlights the subtler and perhaps more important aspects of classical Indian Unani medicine that contributed to the development of the entire body of scientific knowledge. Through an analysis of socio-cultural and historical context, the paper concludes that the contribution of Unani medicine in India lies in:(a) preserving the ancient Greek tradition of medicine; and (b) safeguarding and advancing utilitarian medical science and treatment into the early modern period.